On an algorithmic feasibility of source conditions in iterative methods of solving irregular nonlinear equations - Kokurin, M.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
A relation between an algorithmic feasibility of source conditions in iterative methods for solving irregular nonlinear problems and the «P=NP?» problem is established. On this basis, we estimate the possibilities of polynomial-time algorithmic satisfaction of these conditions.